THE USE OF STUDENT TEAM ACHIEVEMENT DIVISIONS (STAD) TECHNIQUE IN TEACHING READING DESCRIPTIVE TEXT TO THE SEVENTH GRADE STUDENTS OF SMPN 1 KUDU- JOMBANG (RETAIN, 2015)
Abstract Reading is one of the four basic skills of English that have to be mastered by the students. However, it is not easy as it seems. To overcome the students’ problems in learning reading, teachers should be able to choose an appropriate method, strategy, and media to be used to deliver the learning materials. One of the interesting techniques in teaching reading descriptive text is Students Team Achievement Divisions (STAD). STAD is an effective cooperative learning method in which the students are divided into some groups of four. This technique can help the students to comprehend the material easily because they can share knowledge with their friends. This study was to describe the use of Student Team Achievement Divisions (STAD) technique in teaching reading descriptive text to the seventh grade students of SMPN 1 Kudu- Jombang. This study is a descriptive qualitative research. The subjects are the English teacher and the students of VII- A class in SMPN 1 Kudu- Jombang. The data of this study are the result of field notes, the result of students’ reading tasks, and the result of interview. From the results, the researcher concluded that Student Team Achievement Divisions (STAD) technique was interesting for the students. It could build the students’ motivation and interests in learning descriptive text. Besides, STAD technique can help students in improving their reading ability, especially the ability of reading descriptive text. In conclusion, STAD technique is helpful for the students in improving their reading ability. It also helps the students in understanding and mastering a text, especially descriptive texts. It could make the class more active and enjoyable. Key words: Reading, Descriptive Text, and STAD Technique Abstrak Membacaadalahsatudariempatketrampilanutama yang harusdikuasaiolehsiswa.Bagaimanapun, halinitidaksemudah yang terlihat.Untukmengatasimasalahsiswadalambelajarmembaca, guru harusmampuuntukmemilihmetode, strategi, dan media yang tepat yang digunakandenganbahan ajar yang akandiajarkan. Salah satutehnik yang menarikdalampengajaranmembacateksdeskriptifadalahtehnik STAD.STAD adalahmetodebelajarkelompok yang efektif yang dimanasiswadibagimenjadiempatsiswatiapkelompok.Tehnikinidapatmembantusiswauntukmenguasaimateridenganmudahkarenamerekabisaberbagipengetahuandenganteman- temannya.Penelitianinimerupakanpenelitiandescriptive qualitative.Subjeknyaadalah guru bahasaInggrisdansiswakelastujuh A di SMPN 1 Kudu- Jombang, Data daripenelitianiniadalahhasildaricatatanlapangan, hasiltugasmembacasiswa, danhasilwawancara.Dari hasilpenelitianini, penelitimenyimpulkanbahwa STAD technique menarikuntukparasiswa.Tehnikinidapatmembangunmotivasidandayatariksiswadalambelajarteksdeskriptif.Disampingitu, tehnik STAD dapatmembantusiswadalammeningkatkankemampuanmembacanya, terutamakemampuanmembacateksdeskriptif.Kesimpulannya, tehnik STAD sangatmembantusiswadalammeningkatkankemampuanmembacanya.Tehnikinijugamembantusiswadalammemahamidanmenguasaisebuahteks, terutamateksdeskriptif.Tehnikinidapatmembuatkelaslebihaktifdanmenyenangkan. Kata kunci: Membaca, TeksDeskripitf, danTehnik STAD